Spectrophotometric Determination of Gemifloxacin in Pharmaceutical Formulations - Jyothirmayee, D.; Sudhakar Sai Babu, G.; Devala Rao, G. (Asian Journal of Chemistry, 2010)
Two simple and sensitive spectrophotometric methods (method A and method B) in the visible region have been developed for the determination of gemifloxacin in bulk and in pharmaceutical formulations. Method A is based on the reduction of ferric chloride by gemifloxacin and subsequent complexation of ferrous ions with 2,2'-bipyridine reagent to form a red coloured chromogen with an absorption maximum of 520 nm. Method B is based on the reaction of gemifloxacin with ferric alum reagent under acidic conditions to form a yellow coloured product having an absorption maximum of 460 nm. The colour obeyed Beer's law in the concentration range of 6.4-32.0 and 5.1-25.6 μg/mL for method A and B, respectively. When pharmaceutical preparations (tablets) containing gemifloxacin were analyzed, the results obtained by the proposed methods are in good agreement with the labelled amounts. Recovery in both the methods is 98-101 %.